Comorbidities of Chronic Urticaria: A glimpse into a complex relationship - Papapostolou, Niki; Xepapadaki, Paraskevi; Katoulis, Alexander; Makris, Michael (Frontiers in Allergy, 2022)
Chronic Urticaria (CU) is a chronic inflammatory, predominantly mast cell-driven disease, characterized by the development of wheals and/or angioedema for more than 6 weeks. It affects approximately 1%–5% of the total population worldwide and imposes a substantial burden on health-related quality of life, significantly affecting patients' daily life. The economic impact on the health system is also not negligible, with an estimated cost per patient per year of approximately 2.000 $ in the United States. Although the underlying pathophysiology is not fully explored, autoimmune mechanisms have been proposed, including type I (“autoallergy” by means of autoantibodies to self-antigens) and type IIb (autoimmunity). Atopic, autoimmune, and psychiatric disorders are prevalent comorbidities in both children and adults with Chronic Spontaneous Urticaria (CSU). Although malignancies, cardiovascular diseases and other comorbidities have also been reported as associated diseases in patients with CSU, data remain scarce. It is still unknown whether the aforementioned comorbidities share common pathophysiological mechanisms with specific endotypes of CSU. The current review aims to overview current data on comorbidities of CU, and furthermore to comment on the potential linked pathways underlying these diseases.